2005
DOI: 10.1097/01.scs.0000171971.21808.d1
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Soft Tissue Facial Profile in Iranian Females

Abstract: This study was carried out on 100 photographs of Iranian young adult females, ages ranging from 16 to 40 years. Each photograph was scanned, the image was projected onto a computer monitor, and computerized sketches were obtained from them. With the help of a review committee, 10 of the best sketches were selected and analyzed. The linear and angular measurements were made to the nearest 0.5 mm with dial calipers and a standard protractor with 0.5 mm increments. A total of 15 measurements were analyzed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Mafi et al . [9] studied the soft-tissue facial profiles of Iranian women and found some significant differences compared with white women. Because the norms for one ethnic group might not fit for others, in the present study, we aimed to develop soft-tissue cephalometric norms.…”
Section: Introductionmentioning
confidence: 99%
“…Mafi et al . [9] studied the soft-tissue facial profiles of Iranian women and found some significant differences compared with white women. Because the norms for one ethnic group might not fit for others, in the present study, we aimed to develop soft-tissue cephalometric norms.…”
Section: Introductionmentioning
confidence: 99%
“…When facial anthropometric measurements of attractive young Iranian and average white women were compared, lip projection was greater in the Iranians, the nasofrontal angle was larger (ie, the nose was less projected), and their faces were more convex. 31 In another study of attractive versus unattractive Iranians, the attractive women had straighter profiles, less prominent noses with higher nose tips, slightly more protruded maxillae, longer lower faces (or shorter middle faces), more protruded upper than lower lips, and lips positioned closer to the middle of the vertical chin–nose distance. 39 A third study of Iranian women showed that the more attractive the subjects’ profiles were judged to be, the closer their facial ratios are to phi, the Divine Proportion.…”
Section: Resultsmentioning
confidence: 98%
“…The small amount of literature describing the anthropometry of people of Middle Eastern descent is focused on specific geographic regions and includes studies describing Iranian, Lebanese, Saudi Arabian, Egyptian, and Emirati anthropometry 35–42 . Understanding these variations is part of a well‐rounded baseline knowledge, and personalized assessment for each patient is needed.…”
Section: Resultsmentioning
confidence: 99%
“…34 The small amount of literature describing the anthropometry of people of Middle Eastern descent is focused on specific geographic regions and includes studies describing Iranian, Lebanese, Saudi Arabian, Egyptian, and Emirati anthropometry. [35][36][37][38][39][40][41][42] Understanding these variations is part of a wellrounded baseline knowledge, and personalized assessment for each patient is needed. Facial shape, convexity, and proportions are highly variable among Middle Easterners, and perceptions of these features can be shaped by the high degree of ethnic diversity exhibited by people with Middle Eastern heritage.…”
Section: Re Sultsmentioning
confidence: 99%